Secretor Status of ABO Antigens in Saliva of a Defined Group of Iranian Patients with Pemphigus Vulgaris: A Case-Control Study - Sedigheh Bakhtiari; Zahra Yadegari; Marziyeh Kaviyani; Zahra Namazi; Mahin Bakhshi (Scientifica)
Introduction. Pemphigus is a chronic inflammatory and autoimmune disease which can cause blisters and mucocutaneous erosions. ABO secretor refers to those who secrete ABO blood group antigens based on their blood type in body fluids such as saliva, sweat, tears, semen, and serum. Previous studies showed that nonsecretor people are more prone to certain autoimmune diseases. Aim. The aim of this study was to determine the ABO secretor status in the saliva of patients with pemphigus vulgaris. Materials and Methods. This case-control study was conducted on 35 patients with pemphigus vulgaris and 35 healthy controls. The two groups were matched for age and gender. Pemphigus vulgaris diagnosis was confirmed by histopathology and direct immunofluorescence microscopy. ABO blood grouping was done, and 5 ml of unstimulated saliva was collected to determine secretor status. Secretors were recognized from nonsecretors by the Wiener agglutination inhibition test. Results were extracted by using statistical chi-square and Fisher’s exact tests. Results. 16 male and 19 female patients aged 49.43 ± .12.37 years were compared with 16 male and 19 female controls aged 46.43 ± 11.88 years. The most frequent blood group among case and control groups was O (54.3% and 60%, respectively). There was no significant difference in blood groups (P=0.73). 90% of the samples were ABO secretors. The patient group included 31 (88.6%) and the control group included 32 (91.4%) ABO secretors; there was no significant difference between the two groups (P=1.000). Conclusion. In this study, we observed that the people with nonsecretor status in comparison with the people with secretor status are not more susceptible to develop pemphigus vulgaris.